2010
DOI: 10.1007/s10803-010-1076-x
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Friendships at School: Comparing Children With and Without ASD

Abstract: Self, peer and teacher reports of social relationships were examined for 60 high-functioning children with ASD. Compared to a matched sample of typical children in the same classroom, children with ASD were more often on the periphery of their social networks, reported poorer quality friendships and had fewer reciprocal friendships. On the playground, children with ASD were mostly unengaged but playground engagement was not associated with peer, self, or teacher reports of social behavior. Twenty percent of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
313
3
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(361 citation statements)
references
References 40 publications
18
313
3
12
Order By: Relevance
“…they want to be alone or play by themselves). This is in line with a study by Kasari et al (2011), where students with autism spectrum conditions preferred to isolate themselves or were ignored by their peers. The social inclusion of students with SEBD could thus benefit from support in learning how to play with peers during breaks.…”
Section: Discussionsupporting
confidence: 90%
“…they want to be alone or play by themselves). This is in line with a study by Kasari et al (2011), where students with autism spectrum conditions preferred to isolate themselves or were ignored by their peers. The social inclusion of students with SEBD could thus benefit from support in learning how to play with peers during breaks.…”
Section: Discussionsupporting
confidence: 90%
“…For example, given that social difficulties are likely to become more apparent as children enter adolescence and social groupings become more complex (Locke et al 2010), it is questionable whether bullying would decrease with age in ASC, as found in the general bullying research field. Only three studies have explored this, with inconsistent findings (Little 2002;Reid and Batten 2006;Kasari et al 2011). Behaviour difficulties are also associated with being the victim of bullying in the broader literature, and children with ASC are recognised as having aboveaverage levels of such problems (Macintosh and Dissanayake 2006).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…For example, friendship scales such as those developed by Parker and Asher (1993) and Bukowski et al (1994) have been used to describe the characteristics of friendships on the assumption that the relationship exists (Chamberlain, et al, 2007;Kasari, Locke, Gulsrud, & Rotheram-Fuller, 2011;Kuo, Orsmond, Cohn, & Coster, 2011;Wiener & Schneider, 2002;Wiener & Tardif, 2004). The assumption that nomination equates to actual friendship in typically developing children may well be reasonable.…”
Section: Mutual Liking Enjoyment and Shared Interactions In The Clomentioning
confidence: 99%